The effect of pro- and eukaryotic inductors on the synthesis and antimicrobial activity of Acinetobacter calcoaceticus IMV B-7241 surfactants - Pirog, Tatiana; Ivanov, Mykyta; Shevchuk, Tetiana; Blagodyr, Daria (My University, 2024)
By now, the mixed cultivation («co-cultivation») of antimicrobial compound producers with other microorganisms or the introduction of biological inductors in diff erent physiological states (live and inactivated cells, as well as the corresponding supernatants) into the culture medium is a simple, cheap, and eff ective way to increase the synthesis of practically important microbial metabolites and regulate their biological activity. In most studies, researchers use bacterial strains of various species as inductors, however, in recent years, there have been an increasing number of publications reporting the use of eukaryotic inductors, in response to which there’s observed an increase in the synthesis of antimicrobial compounds by the bacterial producers. In addition, the effectiveness of biological inductors depends on the conditions of their cultivation and physiological state

На сьогодні змішане культивування («кокультивування») продуцентів антимікробної сполуки з іншими мікроорганізмами або введення в живильне середовище біологічних індукторів у різних фізіологічних станах (живих та інактивованих клітин, а також відповідних супернатантів) є простим, дешевим та ефективним способом посилення синтезу практично важливих мікробних метаболітів та регулювання їх біологічної активності. У більшості досліджень дослідники використовують штами бактерій різних видів як індуктори, однак останнім часом з’являється все більше публікацій про використання еукаріотичних індукторів, у відповідь на що спостерігається збільшення синтезу антимікробних сполук бактеріями-продуцентами. Крім того, ефективність біологічних індукторів залежить від умов їх культивування та фізіологічного стану
Keywords: дріжджові та бактеріальні індуктори; поверхнево-активні речовини; антимікробна активність; кафедра біотехнології і мікробіології; yeast and bacterial inductors; surfactants; antimicrobial activity